2015
DOI: 10.1111/clr.12557
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and microbiological findings in patients with peri‐implantitis: a cross‐sectional study

Abstract: The results of this study seem to indicate that inadequate oral hygiene and the presence of bleeding from the gingiva/mucosa in patients with dental implant were associated with an higher prevalence of peri-implantitis; moreover, in the patients affected by peri-implantitis, the lack of sufficient height keratinized mucosa (<2 mm) and bone regenerative procedures at implant level were also associated to higher prevalence of peri-implantitis as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

14
137
3
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(159 citation statements)
references
References 46 publications
(60 reference statements)
14
137
3
5
Order By: Relevance
“…Of these, 87 were excluded after review of the title or abstract, and 39 1,9,10,13,14,16‐19,23‐52 full‐text studies were reviewed. Ultimately, 26 studies 9,10,13,14,16‐19,27,36‐52 were included (Table 1), and 13 1,23‐30,32‐35 were excluded for different reasons (12 1,23‐30,33‐35 for not fulfilling the proposed inclusion criteria and one 32 due to its retrospective design). In total, 1,145 patients with 2,134 implants were assessed in the 26 cross‐sectional studies studies 7,9,10,13,14,16‐19,27,36‐46,48‐52 that were included in this review.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of these, 87 were excluded after review of the title or abstract, and 39 1,9,10,13,14,16‐19,23‐52 full‐text studies were reviewed. Ultimately, 26 studies 9,10,13,14,16‐19,27,36‐52 were included (Table 1), and 13 1,23‐30,32‐35 were excluded for different reasons (12 1,23‐30,33‐35 for not fulfilling the proposed inclusion criteria and one 32 due to its retrospective design). In total, 1,145 patients with 2,134 implants were assessed in the 26 cross‐sectional studies studies 7,9,10,13,14,16‐19,27,36‐46,48‐52 that were included in this review.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 21 studies comparing microbial profiles of peri‐implantitis and healthy implants were evaluated using different microbiologic methods: two used methods of cultivation, 37,40 two conventional polymerase chain reaction (PCR), 38,43 three quantitative PCR, 16,17,50 one nested‐PCR, 14 eight DNA hybridization, 9,13,27,36,39,41,42,49 and five DNA sequencing methods 18,19,44,47,51 . The major periodontopathic microorganisms (red complex: Porphyromonas gingivalis [ Pg ], Tannerella forsythia [ Tf ], and Treponema denticola [ Td ]; orange complex: Prevotella intermedia [ Pi ] and Fusobacterium nucleatum [ Fn ]; and other microorganisms: Aggregatibacter actinomycetemcomitans [ Aa ], Eikenella corrodens [ Ec ], Parvimonas micra [ Pm ], and Campylobacter rectus [ Cr ]) were identified in 11 of 21 studies (52.3%) 9,14,16,17,37,39,40,43,49,50,52 . Three studies also evaluated opportunistic microorganisms 37,40,52 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies, overall, fail to demonstrate similar patterns in terms of detected species, frequencies of detection as well as bacterial load. As an example, some studies found no differences in the detection frequencies of Aggregatibacter actinomycetemcomitans (A.a.) , Porphyromonas gingivalis , Prevotella intermedia and Treponema denticola between healthy and diseased implants [49,50]. Others did find differences for A.a., P. gingivalis , Tannerella forsythia , T. denticola [51], Fusobacterium nucleatum , P. intermedia , Peptostreptococcus micros , Campylobacter rectus , Eikenella corrodens , Candida albicans , Prevotella nigrescens , Centruroides gracilis , Capnocytophaga ochracea , Campylobacter concisus , Streptococcus spp.…”
Section: Resultsmentioning
confidence: 99%